First fossil record of the pseudoscorpion family Pseudochiridiidae (Arachnida, Chelonethi, Cheiridioidea) from Dominican amber - Judson, Mark L. I. (Zootaxa, 2007)
Pseudochiridium lindae n. sp. is described from Dominican amber (Miocene), representing the first fossil record of the family Pseudochiridiidae. The extant species Pseudochiridium insulae Hoff, 1964 is newly recorded from the Dominican Republic. Paracheiridium vachoni Vitali-di Castri, 1970 is transferred to the genus Pseudochiridium With, 1906 (n. comb.). The correct publication date for family-group names based on Cheiridiinae Hansen is shown to be 1894.